Investigation of The Connections Between Supply Chain Management Practices and Supply Chain Responsiveness from Competitive Advantage in the Palm Oil Industry - Saputra, Dodi; Lukman, Syukri; Pujani, Vera (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The palm oil industry plays an important role in the global economy as one of the largest agricultural commodities traded in the world. With growing demand for vegetable oil, biodiesel, oleo chemicals and other derivatives, the palm oil industry has become the backbone of many producing countries. As a country with a rapidly growing oil palm plantation sector, Indonesia has great potential to benefit from this industry. However, amidst intensifying global competition and demands to meet higher sustainability standards, it is important for Indonesian palm oil companies to improve their supply chain management practices. Effective supply chain management will help these companies to optimize their operations, reduce costs, and improve efficiency.